ChemInform Abstract: pH‐Controlled and Sulfite Anion‐Directed Assembly of a Family of Cerium(III)‐Containing Polyoxotungstates Clusters. Issue 46 (18th November 2014) - Chen, Wei‐Chao; Wang, Xin‐Long; Jiao, Yan‐Qing; Huang, Peng; Zhou, En‐Long; Su, Zhong‐Min; Shao, Kui‐Zhan
Abstract The cerium(III)‐containing polyoxotungstates (III)—(VII) are characterized by single crystal XRD, IR spectroscopy, XPS, ESI‐MS, and electrochemical measurements.